From Sources to Repertoires: Graecisms in Gabriele D'Annunzio's Poetic Work (Altre Modernità, 2025)
The study and analysis of the lexical material collected in general, historical, and specialized dictionaries represents, for a writer, an essential starting point for the drafting of literary texts, and Gabriele D’Annunzio is no exception. Indeed, he is a paradigmatic case of the relationship between author and lexicographic sources: in fact, the “ulisside (Ulysses’ son) of the word,” according to Bruno Migliorini’s successful definition, continually seeks to transcend language precisely through dictionaries, whose consultation allows him to draw on sources and texts that he does not read and which he uses as the first nucleus of lexical innovation. The poet’s attention to classicisms is very clear, so much so that Latinisms and Graecisms constitute a substantial part of the Vocabolario dannunziano by Giuseppe Lando Passerini, the first lexical catalogue of Gabriele D’Annunzio. The purpose of this contribution is to analyze the Greek component within D’Annunzio’s poetic production through some examples of Graecisms absent from the Italian literary tradition (acroceraunio, aulopide, cline, ecatompilo, peristrofe), coined by the poet (alalà), rarely used (acropolis, aedo, àgora, aulete), and pseudo-Graecisms (rodolent), to show how D’Annunzio created his own repertoire of Graecisms, how much and in what way he drew on lexicographic sources to find them, and what value he attributed to them.
Keywords: Graecisms; D’Annunzio; lexicon; poetry